Smile Computing – A New Religion ( Smile Theory of Everything ) - Gajawada, Satish (Transactions on Engineering and Computing Sciences, 2023)
I would like to thank everything in this universe which is trying to make this place a better place to live. This report is all about “Smile Theory of Everything (SToE)”. In this theory the same thing is given in different formats. A new religion titled “Smile Computing” is invented in this work. In this paper a new title “Smile Computing – A New Religion” is given to the earlier work titled “Smile Theory of Everything”.